1991
DOI: 10.1111/j.1464-5491.1991.tb01674.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Rheology and Cardiovascular Risk Factors in Type 1 Diabetes: Relationship with Microalbuminuria

Abstract: Whole blood and plasma viscosity, erythrocyte aggregation and deformability, plasma fibrinogen, lipids, lipoproteins, apolipoproteins, and measures of blood glucose control were compared between 21 Type 1 diabetic patients with microalbuminuria (overnight albumin excretion rate 30-200 micrograms min-1) and 21 patients with albumin excretion below this range matched for age, sex, and duration of diabetes. Patients with microalbuminuria had significantly higher glycosylated haemoglobin (9.4 +/- 1.6 (+/- SD) vs 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…31 A positive relationship between plasma viscosity and LDL cholesterol, as well as between plasma viscosity and triglycerides, which may be explained by rheological effects of molecules of high molecular mass, are consistent with the results of other studies. 19,[32][33][34][35][36][37] The negative bivariate correlation between plasma viscosity and HDL cholesterol seems to be equivocal but is nevertheless consistent with the findings of other authors. 36 -38 However, the relationship remained no longer significant after performing the MLRA.…”
Section: Discussionsupporting
confidence: 80%
“…31 A positive relationship between plasma viscosity and LDL cholesterol, as well as between plasma viscosity and triglycerides, which may be explained by rheological effects of molecules of high molecular mass, are consistent with the results of other studies. 19,[32][33][34][35][36][37] The negative bivariate correlation between plasma viscosity and HDL cholesterol seems to be equivocal but is nevertheless consistent with the findings of other authors. 36 -38 However, the relationship remained no longer significant after performing the MLRA.…”
Section: Discussionsupporting
confidence: 80%
“…The majority of studies have reported that the development of microalbuminuria/overt diabetic nephropathy is associated with a significant increase in plasma fibrinogen levels, and that a correlation exists between levels and the rate of urinary albumin excretion [14,16,17,[24][25][26][27][28]. Other studies have, however, found no difference in levels between diabetic patients with and without microalbuminuria [18,29,30].…”
Section: Type 1 Diabetes and Fibrinogenmentioning
confidence: 74%
“…It has long been recognised that plasma fibrinogen concentration is elevated in diabetes [40] but a relationship with nephropathy has not always been apparent [41]. Fibrinogen could contribute to the development of nephropathy in a variety of ways: it is the substrate for thrombin in blood coagulation, and animal studies indicate that the fibrinogen concentration at the initiation of coagulation influences the amount of fibrin deposited [42]; in this context it is relevant that low-dose heparin therapy was recently shown to reduce urinary albumin excretion rate in IDDM [43].…”
Section: Discussionmentioning
confidence: 99%